Impact of management practices on reproductive disorders diary animals - SINGH, JASPREET; VERMA, H K; GANDOTRA, V K; SINGH, K B (The Indian Journal of Animal Reproduction, 2023)
Reproductive disorders occurring near and after parturition cause lengthening of intercalving interval and huge economiclosses to dairy farmers. Adoption of good management practices can reduce the incidence of these reproductive disorders. Thepresent investigation was conducted in six agroclimatic regions of Punjab to work out the relation of reproductive disorders with themanagement practices. The data were collected by personally intttviewtng 180 fanners (30 from each agroclimati~ ~).Incidence of reproductive disorders was studied in I 556 animals (I I 57 buffaloes and 399 cows). Incidence of uterine infections,prolapse of genitalia, retention of fetal membranes and abortion was 8.55, 7.32, 10.59 and 7.15% respectively. Significantrelationship of uterine infections with hygienic housing and prolapse of genitalia with hygienic housing and mineral mixturesupplementation was found. Retention of fetal membranes in buffaloes was significantly related with mineral mixture supplementationand colostrums feeding to dam after parturition. Abortion was significantly related with mineral mixture supplementation andhygienic housing.
Keywords: Uterine infections; proplapse, retention of fetal membranes; abortion; mineral mixture, hygienic housing